PENGUATAN MODERASI BERAGAMA MELALUI PERAYAAN HARI SUCI KEAGAMAAN DI SMA NEGERI 1 KUTA UTARA - I Putu Wahyu Suputra; Ferdinandus Nnaduq; I Gede Dedy Diana Putra (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study highlights the importance of strengthening religious moderation in educational institutions as an effort to create harmonious social life amid religious diversity. SMA Negeri 1 Kuta Utara, as a school with students from diverse religious backgrounds, celebrates Saraswati Holy Day and Christmas Holy Day, which have the potential to strengthen religious moderation. Therefore, this study aims to explore the potential, analyze the obstacles, and examine the strategies for strengthening religious moderation through religious holy day celebrations at SMA Negeri 1 Kuta Utara. This study employed a phenomenological approach with a descriptive qualitative research design. Data were collected through observation, interviews, and document studies involving the principal, Hindu religion teacher, Christian religion teacher, and students selected through purposive sampling. Data analysis was conducted through data reduction, data display, and conclusion drawing. The study was supported by James A. Banks’ Multicultural Education Theory to explain the importance of respecting diversity within educational settings. Data validity was ensured through source triangulation and technique triangulation. The findings revealed that the celebration of Saraswati Holy Day and Christmas Holy Day has the potential to strengthen religious moderation through the development of religious tolerance, the enhancement of moderate religious attitudes, and the formation of students’ religious moderation character. However, several obstacles were identified, including limited preparation time, less optimal cooperation among students, and limited time for the implementation of religious activities. To overcome these obstacles, the school implemented several strategies, such as instilling religious moderation values through exemplary behavior, involving students from different religious backgrounds in school activities, and encouraging the active participation of teachers and educational staff in supporting religious events. This study concludes that religious holy day celebrations can serve as an effective medium for strengthening religious moderation and fostering a harmonious, tolerant, and diverse school environment.